Косвенное измерение расхода перекачиваемой жидкости через насосный агрегат - Майстренко, Андрей Васильевич; Светлаков, Анатолий Антонович (НТУ "ХПИ", 2014)
В работе обсуждаются результаты исследования методов косвенного измерения расхода перекачиваемой жидкости насосным агрегатом (НА), основанных на использовании их напорных характеристик. Приведены результаты экспериментальных исследований данных методов, основанных на аппроксимации напорной характеристики алгебраическими полиномами 2-го и 3-го порядков, которые иллюстрируют их работоспособность и пригодность для решения прикладных задач ретроспективного оценивания коэффициентов полиномов, аппроксимирующих напорные характеристики НА.

One of the conditions for the effective operation of pipelines intended for fluid handling by pumping units (PU) is the information on a flow rate through a given section of a pipe. Basing on this information, it is possible to formulate and solve a number of problems, related to the development of mathematical models of technological equipment of pipelines as well as to the numerical simulation of processes in pipelines and, finally, to real-time control of latter. However, for some reasons it is difficult to equip a pipeline with a sufficient number of flowmeters, particularly, due to their complexity and low reliability. Mentioned disadvantages condition the urgency of the problem of development and studying of methods of indirect measurement of flow rate of liquid, pumped with a PU, based on application of their pressure characteristics. The purpose of analytical and experimental studies is the approximation of pressure characteristics by means of algebraic polynomials of various orders, as well as evaluation of the accuracy of approximation. The main results of the performed study are listed below. 1) The indirect method of measuring of the flow rate of a liquid, pumped with a PU, was proposed and investigated. This method is based on the approximation of the pressure characteristics by means of algebraic polynomials that allows approximation of these characteristics with high accuracy. Also, it allows formulation and solution of the problems related to the development of mathematical models of technological processes and pipeline equipment and numerical simulation of latter. 2) The results of the numerical simulation within the proposed method illustrate its performance and suitability for applications in the retrospective mode. These facts open up the broad prospects for the application of the proposed method in automated control systems of pipelines.
Indirect measurement of the fluid flow through the pump unit
Keywords: современные трубопроводы; расходомер; алгебраические полиномы; напорные характеристики НА; коэффициенты полиномов; flowmeter; pumping unit; indirect measurement; polynomial